PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP BIAYA HUTANG STUDI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Pitri yani; Poppy indriani (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2022)
This study aims to determine the effect of Good Corporate Governance either partially or simultaneously on the cost of debt of manufacturing companies listed on the Indonesia Stock Exchange. The data analysis method used is multiple linear regression with 95% certainty. Based on the results of partial multiple linear regression or t test, the variables of institutional ownership, the board of commissioners, the board of directors, and the audit committee partially have no effect on the cost of debt in manufacturing companies. listed on the Indonesia Stock Exchange. Simultaneously or the f test, the variables of institutional ownership, the board of commissioners, the board of directors, and the audit committee simultaneously have no effect on the cost of debt in manufacturing companies listed on the Indonesia Stock Exchange. And the results of the coefficient of determination of the Adjusted R² value of -0.052. This means that the ability of institutional ownership variables, the board of commissioners, the board of directors, and the audit committee to explain the cost of debt, while the rest is influenced by other variables not examined in this study.